Novel Nanomaterials Enable Biomimetic Models of the Tumor Microenvironment. (12th October 2017) - Joyce, Marshall Hunter; Allen, Shane; Suggs, Laura; Brock, Amy
Abstract : In the complex tumor microenvironment, chemical and mechanical signals from tumor cells, stromal cells, and the surrounding extracellular matrix influence all aspects of disease progression and response to treatment. Modeling the physical properties of the tumor microenvironment has been a significant effort in the biomaterials field. One challenge has been the difficulty in altering the mechanical properties of the extracellular matrix without simultaneously impacting other factors that influence cell behavior. The development of novel materials based on nanotechnology has enabled recent innovations in tumor cell culture models. Here, we review the various approaches by which the tumor cell microenvironment has been engineered using natural and synthetic gels. We describe new studies that rely on the unique temporal and spatial control afforded by nanomaterials to produce culture platforms that mimic dynamic changes in tumor matrix mechanics. In addition, we look at the frontier of nanomaterial-hydrogel composites to review new approaches for perturbation of mechanochemical control in the tumor microenvironment.